KAJIAN KOHESI GRAMATIKAL SUBSTITUSI DAN ELIPSIS DALAM NOVEL â€œLASKAR PELANGIâ€ KARYA ANDREA HIRATA - Wiyanti, Endang (Universitas Pendidikan Indonesia, 2016)
AbstractÂ There are several factors that influence a literary work, especially the novel became a best seller beside the content of the story. One of them is the technique of writing. The purpose of this study is to describe and analyze the aspects of cohesion grammatical substitution and ellipsis in the novel of Laskar Pelangi. The research method is qualitative analysis technique to characterize descriptive presentation of data obtained by the research. The results showed the use of language elements such as words, phrases, clauses, and sentences as part of the referrer two sentences in pairs to determine the cohesive relationship has not been evenly distributed. The percentage of grammatical cohesion in the aspect of substitution which includes (1) the substitution of the noun (replacing objects) as many as 31 pairs of sentences or 24,03%; (2) substitution of verbal (replacement verb) in 1 pairs of sentences of 0,78%; (3) substitution clause (clause replacement), the substitution clause consists of a nominal clause as many as 16 pairs of sentences, or 12,4%, verbal clause as much as 4 pairs of sentences, or 3,1%, adjective clause as much as 8 pairs of sentences, or 6,2%, adverbial substitution as many as 17 pairs of sentences, or 13,2%, as many as 1 pair preposional clause sentences or 0.78%, clause numeral as many as 11 pairs of sentences or 8,53%, and aspects of the ellipsis which include nominal ellipsis (deletion of objects) as many as 25 pairs of sentences or 11,38%, verbal ellipsis as much as 2 pairs of sentences, or 1,55%, and ellipsis clause by as much as 4 pairs of sentences or 3,10%. There are 10 pairs of sentences or 7,75% there is no cohesion and declared zero (0).Keywords: grammatical cohesion, substitution and ellipsis, Laskar Pelangiâ€™s novel